'Drawing and playing are not the same': children's views on their activities in Icelandic preschools. Issue 1 (2nd January 2019) - Ólafsdóttir, Sara M.; Einarsdóttir, Jóhanna
Abstract: Play is an important part of early childhood education and has been defined from different perspectives and paradigms. However, definitions of play have been studied more from adults' perspectives than from those of children themselves. This ethnographic research, with children aged three to five years and built on sociological constructs, will explore children's views on play in two preschool settings in Iceland. Video-stimulated recordings were used to support children's conversations about their different activities in the settings, to explore which activities they considered play. Most of the children said that they were playing when they took on roles and could decide what to do with the material. When the children were preparing the play or were drawing, they usually said they were not playing. These findings add to the understanding of play from children's perspectives and are valuable to the research field and for educators working with young children.